Comfort level of house for occupants (comparison between traditional Malay house and terrace house) / Nor Syahril Mubarak Md Nor - Md Nor, Nor Syahril Mubarak (2015)
Thermal comfort is highly subjective. Not only is it subject to personal preference and acclimatisation, but internal and external temperature sensing is integrated such that the overall sensation may be pleasing or displeasing depending on whether the resulting effect is towards or away from the restoration of deep body temperature. Temperature and humidity is a main factors to influencing the comfort condition in the building or house. However, the provide low -cost housing or terrace house has led to considerations in the developments of housing types which are sustainable from economic, social and environmental aspects. Currently, the terrace houses in Malaysia failed to provide satisfactory housing condition to the occupants especially in term of thermal comfort. This study intended to identify and investigate in scope temperature and humidity between terrace house and Traditional Malay house in Malaysia. The studies highlighted the significant and standards level of comfort occupants on both houses. Out of these finding, some recommendations were made for improvements for both houses.